Histone H1 Accumulation in the Avian Bursa of Fabricius Damaged by Infectious Bursal Disease Virus - Garcia-Espinosa, Gary; Tellez, G.; Hargis, Billy M. (International Journal of Poultry Science, 2008)
The present study addresses the localization of histone H1 in tissues sustaining highly apoptotic and necrotic tissue induced by a viral infection of the Bursa of Fabricius as evidence of a possible extranuclear and extracellular movement beyond the nuclei. This potential mechanism of release could be related to previous reports of extranuclear biological activities of this protein. Detection of HH1 by in situ immunostaining was demonstrated as strong and moderate immunoreactivity in the BF of specific pathogen free chickens challenged with Infectious Bursal Disease Virus. The histone H1 immunoreactivity is apparently reduced and principally limited to single or multiple immunoreactive foci when high levels of virus particles are detected. Additionally, the moderate observed immunostaining appears to be associated with cellular aggregates in multiple small localized foci. In virus-infected tissue, those aggregates that display strong and moderate immunoreactivity clearly indicate HH1 immunoreactivity beyond the nuclei and possibly release for dissemination. These results suggest that high tissue damage, through even relatively common viral infections involving the avian humoral immune system, could activate extranuclear and extracellular HH1 release.